Human resource development for rural tourism: a green tourism approach - Ernawati , Ni Made; Arjana, I Wayan Basi; Puspita, Ni Putu Lianda Ayu; Voda, Mihai; Hazra, Samrat (Politeknik Negeri Bali, 2022)
This study aimed to analyze the current human resource (HR) condition in more established tourist villages in Bali, Indonesia, as well as developing a human resource development model that could assist the villages in developing HR for tourism. The research is a qualitative study using 2 sample groups the Community-based Tourism (CBT) management in 5 developed CBT villages in Bali, and the Academics who conducted community services in the villages. The results show that the human resources available are in various stages depend on the phase and the maturity of the CBT village. The 7 training modes suggested in the model could be carried out as a standalone or combined training methods as required that could be carried out by some parties. For a maximum result, these parties that assist villages should work in synergy to contribute in developing rural tourism. The green HR requirement revolves around understanding and practicing ‘green’ in daily life as well as at workplace and profession aiming for achieving the ultimate goal of making the Earth as a safe living place for many generations to come. It is expected that the results of the study could assist villages in developing rural tourism and be used as a reference for personals and officials conducting community service in villages.